Pemberdayaan Remaja Usia Sekolah dalam Upaya Peningkatan Pengetahuan dan Kesadaran Mengenai Kekerasan Seksual di Kecamatan Pauh Kota Padang - Fachrina Fachrina; Maihasni Maihasni; Alfan Miko (Warta Pengabdian Andalas, 2022)
The rise of cases of acts of sexual violence lately needs to be addressed by all parties, not only by the government and related institutions but also by the community. School-age children are very vulnerable to being victims of acts of sexual violence. Unfortunately, these actions tend to be carried out by those closest to the victim, namely father, siblings, uncles, neighbours and friends. Increased knowledge and awareness of children need to be built to prevent acts of sexual violence against them. Understanding is given to children regarding the causes of sexual violence, the impact and methods of prevention, and the perpetrators' characteristics. This activity was carried out to motivate and encourage children to understand preventing and handling acts of sexual violence properly. The targeted audience was school-age children in the Cupak Tangah Village, Padang, under 17 years old. The method of carrying out activities was through lectures/counselling and discussion. Parents and several village staff accompany the presence of children. Participants discussed quite enthusiastically and gained understanding and awareness about acts of sexual violence and its prevention efforts.